(untitled) (Kindle, 2022)
Vitamin D performs its immunomodulatory effects on T lymphocytes, by inhibiting the synthesis of pro-inflammatory Th1 cytokines (IL-1, IL-2, IL-6, IL-12, IFN-γ, TNF-α, and TNF-β), and triggering the synthesis of anti-inflammatory regulatory Th2 cytokines (IL-4, IL-5, and IL-10). Therefore, vitamin D potentiates the innate immune system and regulates the adaptive immune system, mainly by triggering the split to Th2 and regulatory T cells (Tregs), over the Th1 and Th17 lymphocytes differentiation, via direct and indirect effects on naive CD4+ cells. The general finding is an evident effect of switching capacity, from a pro-inflammatory autoimmune to an anti-inflammatory tolerogenic immunological effect.